Implants with a Laser-microgrooved Collar Placed in Grafted Posterior Maxillary Extraction Sockets and in Crestally Grafted Sinuses: a 5-Year Multicentre Retrospective Study - Renzo Guarnieri; Luca Savio; Alessandro Bermonds; Luca Testarelli (eJournal of Oral Maxillofacial Research, 2020)
Objectives: The aim of this retrospective multicentre cohort study was to compare clinical outcomes, soft tissues conditions and differences in marginal bone loss between implants with a laser-microgrooved collar placed in posterior maxillary extraction sockets grafted by 4 to 5 months, and in posterior maxillary pristine bone (spontaneously healed posterior maxillary extraction sockets) by means of osteotome-mediated sinus floor elevation, over a period of 5 years after functional loading.